COVID-19 HEALING METHOD OF COVID-19 TRADITIONAL MEDICINE IN THE VIEW OF SCIENTIST-SANTRI MEDICINE PRACTITIONERS - Derry Ahmad Rizal; Siti Mufida; Heru Sulistya; Rachmad Resmiyanto; Rizal Al Hamid (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
This paper aims to understand and analyze the handling and treatment and treatment of Covid-19 in Indonesia according to traditional healing practitioners in Java. The spread of the Covid-19 virus has hit Indonesia since March 2020. The spread of the Covid-19 virus is very troubling, and even inhibits and totally paralyzes all community activities, ranging from the economy, education to work, and others. This study uses qualitative methods and field observations in the form of conducting in-person interviews with several healing practitioners in Java, especially in Yogyakarta related to their views or perspectives on the virus and Covid-19 drugs. The results showed that traditional healing practitioners in Java used several herbs that they thought were able to overcome or be used as Covid-19 drugs. The herb is in the form of spices, plants, and some folk remedies from the ancestors. They are trying to offer a cure for Covid-19 by returning to back to nature. In addition, they also try to rationalize the pain that occurs when the human body's immunity decreases or energy is unbalanced, is the result of violations of natural laws by humans themselves.